2015
DOI: 10.1080/09546553.2015.1069671
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Matters: The Effects of Targeted Killings on Militant Group Tactics

Abstract: Targeted killings have become a central component of counterterrorism strategy. In response to the unprecedented prevalence of this strategy around the world, numerous empirical studies have recently examined whether "decapitating" militant groups with targeted killings is strategically effective. This study builds on that research program by examining the impact of targeted killings on militant group tactical decision-making. Our empirical strategy exploits variation in the attack patterns of militant groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 12 publications
2
40
0
Order By: Relevance
“…Moreover, some research looking at the consequences of decapitation reaches different conclusions. For example, Abrahms and Mierau (2017) found that in the immediate aftermath of drone strikes aimed at neutralizing the leadership of terrorist groups, attacks moved from military to civilian targets, effectively increasing their overall lethality. The authors interpret this result as evidence that compared to higher-level group LEADERS, FOLLOWERS AND VIOLENCE IN EXTREMIST GROUPS 8 members, lower-level members of organizations who take over leadership roles after targeted killings are more prone to use violence.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Moreover, some research looking at the consequences of decapitation reaches different conclusions. For example, Abrahms and Mierau (2017) found that in the immediate aftermath of drone strikes aimed at neutralizing the leadership of terrorist groups, attacks moved from military to civilian targets, effectively increasing their overall lethality. The authors interpret this result as evidence that compared to higher-level group LEADERS, FOLLOWERS AND VIOLENCE IN EXTREMIST GROUPS 8 members, lower-level members of organizations who take over leadership roles after targeted killings are more prone to use violence.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Hepworth (2014) finds no evidence of retaliation after the killing of top-tier al Qaeda leaders. Abrahms and Potter (2015) as well as Abrahms and Mierau (2015) find that drone strikes led to a decline in attacks against military targets in the Afghanistan-Pakistan tribal regions, but that they also increased indiscriminate targeting. Jenna Jordan (2014) argues that the attacks against al Qaeda are ineffective and likely to be counterproductive.…”
Section: The Effectiveness Of Leadership Decapitationmentioning
confidence: 99%
“…Still, researchers need to investigate not just whether leadership decapitation "works", but how this counterterrorism strategy and others may actually exacerbate the terrorism threat. In recent work, I have tried to shed light in this area by demonstrating how killing the leaders of militant groups tends to make them more tactically extreme (Abrahms and Mierau, 2017;Abrahms, 2018). Now that academics have a firmer understanding of our terrorist enemies, we need to redouble efforts to understand how to combat them or at least not to contribute to the problem.…”
Section: Discussionmentioning
confidence: 99%